Lack of insight may predict impaired decision making in manic patients. - Adida, M; Clark, L; Pomietto, P; Kaladjian, A; Besnier, N; Azorin, J; Jeanningros, R; Goodwin, G (2008)
OBJECTIVES: The tendency to engage in risky behaviours is a core feature of the manic episodes of bipolar disorder. The aim of this study was to establish whether this characteristic can be quantified with a laboratory measure of decision making [the Iowa Gambling Task (IGT)] and to determine clinical correlates of the IGT performance in mania. METHODS: Inpatients with acute mania (n = 45) and healthy volunteers (n = 45) were assessed on the IGT. Affective symptomatology was assessed with the Young Mania Rating Scale and Hamilton Depression Rating Scale, and item scores were subjected to factor analysis. Multivariate regression was used to assess clinical predictors of impaired decision making in the manic patients. RESULTS: On the IGT, manic patients selected more cards from the risky decks than healthy controls, and showed little capacity to learn from incurred losses. In a multivariate analysis, impaired decision making ability in the manic patients was significantly predicted by a symptom factor associated with lack of insight. CONCLUSIONS: Manic patients clearly show defects in decision making, which are strongly related to their lack of insight. Neural circuitry supporting effective decision making, including the ventromedial prefrontal cortex and somatosensory cortex, may be implicated in the pathophysiology of acute mania.